2019
DOI: 10.26501/jibm/2019.0902-012
|View full text |Cite
|
Sign up to set email alerts
|

Muslim Consumers Style Inventory: A Case from Pakistan

Abstract: The primary objective of the study is to investigate the Muslim consumers' style inventory. An allied objective of this study is to test the reliability and validity of Consumer Style Inventory (CSI) in an economically developing country like Pakistan. For this purpose, data was collected from university graduate and undergraduate students. Factor reduction technique was used in SPSS to examine Muslim consumers' style inventory. Findings of the study indicate that Muslim consumers are partially different from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…alāl" food can isolate a consumer from the Muslim community, possibly affecting their relationships with family and friends, as some members may treat them as a social "outcast" because they do not meet the standards of Islam (Salman & Siddiqui, 2014). Shafique et al (2019) studied Muslim consumers' behavior in style shopping inventory and found that Muslim consumers tend to be less impulsive and buy in a less recreational way than non-Muslim consumers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…alāl" food can isolate a consumer from the Muslim community, possibly affecting their relationships with family and friends, as some members may treat them as a social "outcast" because they do not meet the standards of Islam (Salman & Siddiqui, 2014). Shafique et al (2019) studied Muslim consumers' behavior in style shopping inventory and found that Muslim consumers tend to be less impulsive and buy in a less recreational way than non-Muslim consumers.…”
Section: Literature Reviewmentioning
confidence: 99%